Addressing Child Labor in the Workplace and Supply Chain - International Finance Corporation (International Finance Corporation, Washington, D.C., 2017)
The note seeks to provide companies who are interested in addressing the topic of child labor with a range of basic, good practice approaches that other businesses have successfully applied in addressing the issue of harmful child labor in their workplaces and those of their vendors and suppliers. According to International Labour Organization (ILO) statistics published in May 2002, there are an estimated 352 million children aged 5-17 engaged in some form of economic activity around the world. Of these 352 million, 246 million are either (i) below their country's minimum age for employment; (ii) working in occupations that jeopardize the physical, mental or moral well-being of a child; or (iii) working as slaves, prostitutes or bonded laborers. Action against harmful child labor tends to be most effective when it involves a range of stakeholders from the public and private sectors as well as civil society. Government has a role to play in drafting and enforcing laws and providing educational opportunities. Civil society performs a valuable function by filling gaps in government services and by lending a voice to community concerns. Companies are increasingly working together with government and civil society to address complex issues such as child labor. This note does not constitute policy or contain policy requirements; rather its purpose is to share learning and experiences with a private sector audience. Specifically, the note addresses what constitutes harmful child labor; its Implications for the private sector; how to address the issue in the workplace; how to respond when harmful child labor is detected; how to manage supply chain risks; targeting corporation vendor compliance. The note provides a case study on eliminating harmful child labor in the carpet industry, the Obeetee Approach, and examines harmful child labor, forms and effects. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.